2014
DOI: 10.1111/bju.12632
|View full text |Cite
|
Sign up to set email alerts
|

Renal function evaluation in patients undergoing orthotopic bladder substitution: a systematic review of literature

Abstract: Renal function (RFn) after orthotopic bladder substitution (OBS) is a critical point to be assessed. We performed a systematic review of MEDLINE for full length peer reviewed English articles from the year 2000 till January 2013. We included only original articles and excluded reviews, editorials and replies and abstracts presented in conferences. The outcome is formulated in research questions; what is the status of RFn after OBS? Which is better, the direct free-refluxing or anti-refluxing ureteroileal anast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
(118 reference statements)
0
9
0
Order By: Relevance
“…In our study, renal function deterioration was seen in 53.3% of patients in the first year and 41.1% of patients in the fifth year. (1,2,3,24,25,26,27). Although the preoperative and postoperative eGFR values were statistically insignificant, the development of postoperative urinary tract obstruction and postoperative urinary tract infection were the only significant risk factors for renal deterioration.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, renal function deterioration was seen in 53.3% of patients in the first year and 41.1% of patients in the fifth year. (1,2,3,24,25,26,27). Although the preoperative and postoperative eGFR values were statistically insignificant, the development of postoperative urinary tract obstruction and postoperative urinary tract infection were the only significant risk factors for renal deterioration.…”
Section: Discussionmentioning
confidence: 95%
“…Of these, urinary tract obstruction due to ureteroileal stricture is more common. Performing an antirefluxing ureteroileal anastomosis has long been thought to lead to increased ureteroenteric stricture rates, possibly due to the increased dissection and handling of the ureter during surgery which lends itself to ischemic changes [25]. However, neither the more commonly used free-refluxing method nor the antireflux technique have proven superior to the other.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in attempt to homogenize the cohort, we performed a sub-analysis excluding patients underwent nephroureterectomy with cystectomy, in this context, orthotopic substitution came into focus. It has been reported that the link between orthotopic substitution and renal function deterioration was attributed to the development of UIA stricture and to a less extent, pyelonephritis ( 27 ). Recently, there has been a focus on the effect of uri-nary diversion type on renal function.…”
Section: Discussionmentioning
confidence: 99%